Money Management Practices of Senior High School Teachers at A Public School: A Case Study - Robles, Mercy P.; Polinar, Mark Anthony N. (Future Science / FSH-PH Publications, 2024)
All individuals, regardless of their level of education and employment status, should practice effective management of financial resources. This is essential for setting and attaining financial objectives and making prudent financial decisions. A case study was conducted to deeply analyze the money management practices from the lens of senior high school teachers at a public school in Cebu City, reflecting practices concerning budgeting, saving, spending, debt repayment, and retirement. There were ten key informants, five (5) from Grade 11 and another (5) from Grade 12. These individuals have qualified to be key informants in the study as they meet the inclusion criteria set by the researchers. During the data analysis, notable themes in every indicator were found: needs and wants, meeting financial obligations, using a piggy bank, creating reserves for debt settlement, and preparation for retirement through saving. This shows that despite facing ongoing challenges, these individuals still have the courage and full awareness to manage their money correctly, allowing them to make sound financial decisions. Understanding fundamental finance principles will enable educators to transform their budgets into actionable strategies, establish achievable savings targets, and prioritize repaying debts. This knowledge equips them to more effectively navigate financial hurdles like living expenses, healthcare costs, and planning for retirement. Furthermore, properly implementing effective personal financial planning can enable teachers to attain financial growth and security, leading to increased independence, reduced financial and emotional stress, and an enhanced quality of life.